Towards a theory of development - Minelli, Alessandro, Ed; Pradeu, Thomas, Ed (Oxford University Press, 2014)
Is it possible to explain and predict the development of living things? What is development? Answers to these innocuous questions are far from straightforward. To date, no systematic, targeted effort has been made to construct a unifying theory of development. This text offers a unique exploration of the foundations of ontogeny by asking how the development of living things should be understood. It explores the key concepts of developmental biology, asks whether general principles of development can be discovered, and examines the role of models and theories. This book analyses a wealth of approaches to concepts, models and theories of development, such as gene regulatory networks, accounts based on systems biology and on physics of soft matter, the different articulations of evolution and development, symbiont-induced development, as well as the widely discussed concepts of positional information and morphogenetic field, the idea of a 'programme' of development and its critiques, and the long-standing opposition between preformationist and epigenetic conceptions of development. --